The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.jhazmat.2009.11.133
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating fly ash and acidic process waste water in brick structure

Abstract: a b s t r a c tFly ash contains metals such as cadmium, iron, lead, aluminum and zinc in its structure in appreciable amounts. These metals can leach out into surface and ground waters if fly ash is not properly disposed of. A similar problem also exists for acidic process waste waters discharged by numerous industries. The purpose of this study was to utilize such wastes as additives in the production of construction quality bricks for the purpose of waste elimination. The bricks produced were subjected to fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The proposed explanation of dropped sensitivity to drying is improved binding of the particles due to pozzolanic reaction in contact with moist [23]. The other researches also concluded that moist diffusion in bricks with fly ash addition is improved [4].…”
Section: Changes Observed In Shaping and Drying In The Airmentioning
confidence: 99%
“…The proposed explanation of dropped sensitivity to drying is improved binding of the particles due to pozzolanic reaction in contact with moist [23]. The other researches also concluded that moist diffusion in bricks with fly ash addition is improved [4].…”
Section: Changes Observed In Shaping and Drying In The Airmentioning
confidence: 99%
“…The disposal of bottom ash is a matter of great concern, as the dumped ash is highly unsuitable for the agricultural uses and it makes the agricultural land barren and unproductive [5]. So much research is being conducted from more than two decades for the use of coal ashes in construction such as cement and brick production [6,7]. Many researchers have also studied the use of bottom ashes for the removal of dyes and organic pollutants from waste water [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The study considered the 302 cases available in the literature on the usage of fly [1,[3][4][5][7][8][9][10][11][12][13][14][15][18][19][20][21][22][23][24][25][26][27][28][29][30], bottom ashes [2,6,24,30], and pond ashes [5,13,14,31] in clay bricks.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…Particle size distributions of coal ashes were determined by wet [5,6,13,14,22,24,28,30], and dry sieving [8], while in some studies [1,3,9,11,12,25,29], the samples were sieved or ground and certain fractions were used for the brick production. In the present study, the maximum particle size of the ash (PS max ) used for brick production was considered as the input parameter.…”
Section: Input and Output Parametersmentioning
confidence: 99%
See 1 more Smart Citation